UPAYA PENYELESAIAN SENGKETA WARIS TANAH ADAT PADA MASYARAKAT KARO (STUDI DI PN KABANJAHE) - NOVIRA BR. SEMBIRING (PREMISE LAW JURNAL, 2016)
The Karonese who domicile in Karo Regency have their customary legal system which concept of settling the problem in the form of ‘runggun’ did not work as negotiation for consensus principality. It is occurs as a result of still many complaints about the disputes of the inheritance of adat land in the Kabanjahe District Court. The research used judicial normative method, supported by field study. The enabling factors of the dispute in inheritance of adat land which was settled in the Kabanjahe District Court were as follows: the dispute could not be settled by ‘runggun’, the lack of trust in the decision in ‘runggun’, and the need for legal legitimacy on the dispute settlement. The Kabanjahe District Court provides the settlement by mediation and in the form of verdict and both of them are used by the Karonese community although the latter is commonly used. It is occured by the obstacles faced by the Kabanjahe District Court which consist of two problems; external obstacles comprise the participation of the conflicting parties and their attorneys, laws, and the lack of socialization about law on land and land registration. Internal obstacles comprise judge’s prudence, judge’s professionalism, and court’s administration. Keywords: Inheritance of Adat Land, Dispute Settlement, Runggun